Strategies for Activating the Sale of Local Specialty Foods Using TV Media and Digital Platforms: A Case Study of LG HelloVision’s ‘Season Market’ (aSSIST Business Review, 2026)
(1) Background/Purpose: Korea’s rural regions face an existential crisis of regional depopulation, driven by the outflow of young populations and a lack of employment and education opportunities. This study examines how the activation of local specialty food sales through TV media and digital platforms can serve as a practical mechanism for regional economic revitalization. (2) Methodology: The study employs a qualitative case-study approach, analyzing three cases: (i) the Ministry of Oceans and Fisheries’ ‘Korea Fisheries Grand Sale’ national discount campaign; (ii) Haenam County’s integrated local specialty promotion strategy including its direct-sales online mall ‘Haenam Miso’; and (iii) LG HelloVision’s regional cable channel commerce brand ‘Season Market’ (Jeoljangteo) and its co-development of ‘Ttangkkeut-maeul Haenam Kimchi’ with Haenam County. (3) Findings: Central government discount campaigns (Korea Fisheries Grand Sale) are effective at stimulating total sales volume but disproportionately benefit downstream distributors and retailers rather than primary producers, due to the complex multi-stage distribution structure. Haenam County achieved high-income farm household growth by pursuing two complementary strategies: direct transaction (29.4% direct-sale ratio for sweet potato, approximately 15 times the national average) and value-added processing (salted cabbage commands 8 times the per-tonne price of fresh cabbage). LG HelloVision demonstrated that a cable TV operator can leverage its broadcast platform, subscriber data, and digital ecosystem to open new distribution channels for local specialties at lower commissions than conventional home shopping, while co-developing processed products with local governments to generate greater added value. (4) Originality/Value: This is among the first studies to integrate media platform capabilities with local government agricultural promotion strategy in the Korean context. Practical recommendations are derived for policymakers, local governments, and media-platform companies.
Keywords: local specialty food; regional depopulation; direct transaction; value-added processing; TV commerce; digital platform; local economic revitalization; LG HelloVision; Haenam County